Antihistamines: promising antidotes of organophosphorus poisoning - Ojha, Shreesh; Sharma, Charu; Nurulain, Syed M (Vojenské zdravotnické listy, 2014)
Organophosphorus (OP) is a large group of compounds with a wide variety of applications. The group comprises insecticides, pesticides and nematicides etc. in addition to deadly poison OP warfare chemicals like sarin and tabun. Thousands of casualties have been reported globally each year by the unintentional and intentional use of OP compounds. Uses of deadly poison OP like sarin by terrorists groups and irresponsible regimens have been documented as well. The threat always exists. The mainstream therapy includes administration of atropine, pralidoxime and bezodiazepines in addition to general supportive measures. Despite this standard therapy, the mortality rates of OP poisoning are still high. Different approaches and methodologies have been postulated and introduced as an alternative to standard therapy but none could replace the existing standard therapy. The present short review examined the possibility of usage of antihistamines as alternate to atropine. Pros and cons have been discussed. The study suggests that some of the first generation antihistamines like promethazine and diphenhydramine may be effectively used as antidote for OP poisoning depending upon the degree of poisoning. They may have several advantages like inexpensive, systematically and centrally acting anticholinergic antihistamines, readily crosses bloodbrain barrier, and large quantities of the drug exist in most hospitals and pharmacies, providing a reservoir in the event of a mass casualty event. However, further clinical studies and evidences are warranted.
Keywords: antidota; Organophosphate Poisoning; Antidotes; Animals; Histamine Antagonists; Diphenhydramine; lidé; difenhydramin; promethazin; antagonisté histaminu H1; Histamine H1 Antagonists; Humans; otrava organofosfáty; antihistaminika; zvířata; Promethazine